Formulation and evaluation of clonidine hydrochloride transdermal patch - Sitaula, Barsha; Thapa, Achyut Bikram; Budhathoki, Uttam (Kathmandu University Journal of Science Engineering and Technology, 2025)
Clonidine, an antihypertensive agent, undergoes extensive first-pass metabolism via the oral route. Transdermal delivery overcomes this limitation, providing steady plasma levels, improved patient compliance, and reduced side effects. Its favorable physicochemical properties, including low molecular weight (230.09 g/mol), moderate lipophilicity (Log P ≈ 2), and low daily dose requirement, facilitate permeation through the stratum corneum, with a reported transdermal flux of 0.0710 {\textmu}g/mm{{}^2}/hr. The objective of this study was to formulate and evaluate a sustained-release transdermal patch of clonidine hydrochloride using the solvent casting method. Formulation development was carried out in three stages guided by Central Composite Design. 13 dummy patches with varying HPMC and PEG 4000 concentrations optimized folding endurance, followed by 8 API-containing patches with different enhancer combinations (DMSO, Tween 80, SLS, BZC) to identify the best formulation. The optimized formulation exhibited uniform weight (0.4887 ± 0.0086 g), consistent thickness (0.52 ± 0.04 mm), adequate moisture content (13.94 ± 0.77%), high folding endurance (403.6 ± 10.7), and a smooth, transparent surface. Drug assay and content uniformity were within acceptable limits (100.94% and 92.39 ± 2.78%, respectively). In vitro permeation studies across goat skin revealed higher flux (0.105 {\textmu}g/mm^2}/hr) and cumulative drug permeation (2.391%) compared to the control (0.036 {\textmu}g/mm^2}/hr, 0.761%). The release followed zero-order kinetics (R^2=0.8187), confirming controlled and sustained drug delivery from the optimized patch. The optimized transdermal patch shows superior drug release and permeation compared to the control.